SOCIAL CONDITIONS OF FILM CRITICS IN SOUTH KOREA FROM 2000 TO 2020 - WON, Eunyoung (International Journal of Korean Humanities and Social Sciences, 2021)
This paper empirically analyzes the social status of film critics in the Korean film industry. Film critics contribute to the creation of films as producers of specific values in film art by producing cinematographic discourse. Then how does one become a film critic? How does the film critic space operate – which can be understood as structured based on the development of the market for film magazines in the 1990s? The result of quantitative and qualitative analysis of the social recruitment of film critics from 2000 to 2020 shows that those who attained the legitimate status of film critic by winning awards in contests possess a high level of academic capital. It was also found that the location of higher education among these laureates was mainly concentrated in Seoul. Although film critics are not fully institutionalized and have an artistic mission to some extent, to access the profession of film criticism, they need to be controlled by established film critics who share similar cultural and symbolic capital each other. This suggests that symbolic power exists in the world of film criticism and that the structure can be reproduced through gatekeeping by the owners of symbolic power.